Analisis Potensi Pasar Komoditas Garam di Pantai Selatan Kabupaten Malang - Abd. Aziz Amin; Adi Tiya Yanuar; Zulkisam Pramudia; Yogita Ayu Dwi Susanti; Rika Kurniaty; Riski Agung Lestariadi; Lukman Hakim; Citra Satrya Utama Dewi; Tri Budi Prayoga; Gatot Ardian; M. Nasirudin Yahya; Muhammad Amenan; Andi Kurniawan; Lutfi Ni’matus Salamah (Current Trends in Aquatic Science, 2022)
Salt is one of the marine mineral products that has great potential in Indonesia. Salt production in Indonesia is mostly located on the island of Madura and the north coast of Java. Indonesia still imports salt to meet salt needs, especially for industrial salt needs. In increasing national salt production, one of the strategic steps that need to be taken is to increase the area of ??salt ponds in Indonesia. To increase the area of ??salt land, one important strategy is to open salt ponds outside the North Coast of Java and Madura Island. One alternative location is the beaches in the southern region of Java Island. Salt production on the South Coast of Java has not been done much. On the South Coast of Malang Regency, there is no salt production business. The creation of salt production in the South Coast of Malang Regency needs to be based on an analysis of market potential. This study aims to analyze the market potential of salt commodities in the South Coast of Malang Regency. This study is the first study to analyze the market potential for the development of salt production in the South Coast of Malang. The results of this study indicate that the main market potential for salt production in the South Coast of Malang is salt for fishery activities and salt for livestock. In addition, there is a potential market for salt education activities and consumption salt. Based on the results of this study, the development of the salt commodity market in the South Coast of Malang can be developed with a Niche Marketing approach.